Normatividades e instituciones eclesiásticas en el virreinato del Perú, siglos XVI-XIX, - Duve, Thomas; Albani, Benedetta; Danwerth, Otto (Global perspectives on legal history ;, 2020)
The volume focuses on the viceroyalty of Peru (16th-19th centuries). Scholars from different disciplines present innovative studies on the history of religious normativity and its practices.